Hungry Heartland: The Cuba Story - Bresser, Jack; Schippers, Desiree; Yu, Han; Joglekar, Shreepad; Hallaq, Tom G. (Kansas State University, 2018)
Most of the 150 or so residents of Cuba, Kansas are above the age of 60. Citizens grow their own vegetables in home gardens and share the surplus with their neighbors. The Cuba Cash Store is a central gathering place and the lifeblood of the community. Closing down the store means closing down the town. This story is told through the voices of the townsfolk.
Keywords: food deserts; rural communities; senior communities